Effect of Foreign Direct Investment on Growth-Unemployment Nexus: Anglų k. - Kadiša, Tomas; Butkus, Mindaugas; Aleksandravičienė, Akvilė (Socialiniai tyrimai, 2021)
This paper examines the effect of foreign direct investment (FDI) on the growth-unemployment nexus. A review of previous contributions on Okun’s law uncovered which aspects of international relations are more prone to affect growth-unemployment nexus. It was found that inward FDI and outward FDI are most likely to affect this nexus. EU-28 panel data and interactive model with pooled OLS estimator were used to empirically test whether both inward and outward FDI moderates the relationship between growth and unemployment. The estimations showed that, as expected, FDI weakens the effect of growth on unemployment. Moreover, with an increase in FDI, the effect of growth on unemployment becomes less statistically significant.